A rule-based semantic approach for data integration, standardization and dimensionality reduction utilizing the UMLS: Application to predicting bariatric surgery outcomes. (March 2019) - Modaresnezhad, Minoo; Vahdati, Ali; Nemati, Hamid; Ardestani, Ali; Sadri, Fereidoon
Abstract: Utilization of existing clinical data for improving patient outcomes poses a number of challenging and complex problems involving lack of data integration, the absence of standardization across inhomogeneous data sources and computationally-demanding and time-consuming exploration of very large datasets. In this paper, we will present a robust semantic data integration, standardization and dimensionality reduction method to tackle and solve these problems. Our approach enables the integration of clinical data from diverse sources by resolving canonical inconsistencies and semantic heterogeneity as required by the National Library of Medicine's Unified Medical Language System (UMLS) to produce standardized medical data. Through a combined application of rule-based semantic networks and machine learning, our approach enables a large reduction in dimensionality of the data and thus allows for fast and efficient application of data mining techniques to large clinical datasets. An example application of the techniques developed in our study is presented for the prediction of bariatric surgery outcomes. Highlights: We developed a system that utilizes semantic networks for reducing data dimensionality. Decision trees, regression and neural networks were used to find the significant variables and thus reduce the dataset. We apply our technique to variable subset selection using a hybrid method combining statistical and semantic approaches.